The Neotropical species of Xanthopimpla Saussure (Hymenoptera: Ichneumonidae: Pimplinae) - Gómez, Isrrael C.; Sääksjärvi, Ilari E.; Broad, Gavin R.; Puhakka, Liisa; Castillo, Carol; Peña, Carlos; Pádua, Diego G. (Zootaxa, 2014)
Xanthopimpla Saussure, 1892 is one of the largest and best studied genera of the family Ichneumonidae. It is most species rich in the Oriental and Afrotropical regions with only a few species occurring in Central and South America. The present study reviews the Neotropical species of the genus including descriptions of four new species from Amazonia and Northeast South America. We define a new species group: the amazonica species-group, to accommodate the following five species: X. amazonica Gómez, Sääksjärvi & Veijalainen, X. guianensis Gómez & Sääksjärvi sp. n., X. jussilai Veijalainen, Sääksjärvi & Broad, X. pucallpensis Gómez & Sääksjärvi sp. n. and X. vidali Gómez sp. n. The aurita species-group, which had hitherto been regarded as the only species-group in the Neotropical region, is currently represented by five species: X. allpahuaya Gómez & Sääksjärvi sp. n., X. aurita Krieger, X. craspedoptera Krieger, X. rhabdomera Townes and X. spiloptera Krieger. The Andean species X. peruana Krieger is established as an unplaced species outside of the amazonica and aurita species-groups. A key to Neotropical species-groups and species of Xanthopimpla is provided. Xanthopimpla aurita is recorded for the first time from Ecuador and Colombia and its extensive distribution is discussed. Xanthopimpla amazonica, X. craspedoptera and X. jussilai are recorded for the first time from Brazil; X. amazonica is recorded for the first time from French Guiana; X. spiloptera is recorded for the first time from French Guiana and Peru, and X. rhabdomera is recorded for the first time from Peru.